Impact of a Terrorist Attack on the Mental Health of Directly Exposed French Adolescents: Study Protocol for the First Step of the AVAL Cohort Study - Grenon, Marion; Consigny, Maëlys; Lemey, Christophe; Simson, Jean-Pierre; Coulon, Nathalie (Frontiers in Psychiatry, 2019)
Background: Several terrorist attacks have recently taken place in France and Europe. Various studies have shown a high prevalence of Post-Traumatic Stress Disorder (PTSD) and other psychiatric disorders among the victims of these attacks. Nevertheless, research in this field is scarce and no cohort study has been conducted yet to evaluate the impact of a terrorist attack on teenagers directly exposed to this type of events. Therefore, we decided to work on the AVAL cohort study, in order to measure the psycho-traumatic impact of this attack and to describe these adolescents’ health care pathways. Material and method: The 53 students of a French high school who were directly exposed (criterion A1 of PTSD in DSM-5) to the terrorist attack perpetrated in London on March 22, 2017 constitute the target population of this monocentric cross-sectional observational study. We decided not to include the three students who were physically wounded and, therefore, didn’t have the same sensorial exposition. The primary endpoint will be the prevalence of PTSD 12 to 15 months after the attack, measured by the PCL-5 (Post-traumatic stress disorder Check-List for DSM-5) global severity score: the diagnosis of PTSD will be retained when the score is > 32. We will also use an extensive battery of clinical tests to assess the prevalence of anxiety disorders, mood disorders, sleep disorders, addictions, suicide risk and alterations in social, family and school functioning 12 to 15 months after the attack. We will also describe these adolescents’ health care pathways since the attack and collect data from the clinical evaluation performed during the initial intervention of the medico-psychological emergency cell, within 10 days after the attack. Discussion: The findings of this study are intended to provide epidemiological data about the psycho-traumatic impact of a terrorist attack on the mental health of directly exposed adolescents and to describe these adolescents’ health care pathways, thus contributing to improve the immediate, post-immediate and delayed response strategies after a major psycho-traumatic event involving adolescents (and in particular after terrorist attacks), as well as the identification and psychiatric care of the young survivors requiring specialized care.